A mathematical model of demand with unpredictable salt supply: a case study in Madura - Iffan Maflahah; Budisantoso Wirjodirdjo; Putu Dana Karningsih (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
The proposed mathematical model aims to optimize the amount of demand based on the uncertainty of salt supply to meet the needs of salt in society. This study uses an econometric approach to model the supply and demand for salt based on the uncertainty of the amount of supply. The research results are the salt productivity model used to build a salt availability model. Meanwhile, the salt demand model is built based on past data about the number of requests for each period. The demand and supply functions for salt use a two-variable linear equation system. The salt field productivity models follow a quadratic polynomial pattern according to the difference in seasons at each time. The demand and supply of salt model follows a linear regression. The supply of salt in Indonesia is uncertain at any time. But, the demand for salt increased at the time. It is necessary to model the demand and supply of salt to meet the demand for salt